Spatial structure and prediction of Land use change considering development projects in urban promotion districts - Yoshitaka Kajita; Masaya Kawano; Tetsunobu Yoshitake; Hiroshi Tatsumi; Satoshi Toi (European Regional Science Association (ERSA), 2004)
n this paper, the actual conditions and the change structure of land use by using mesh data are studied in urban promotion area in a local hub city of Fukuoka, Japan. Firstly, all meshes are classified into 15 patterns based on distribution of land use. Then, transition probability models are made out based on the change of these 15 patterns. The Change structure of land use in an area depends on whether development projects are carried out or not. Therefore, all of the meshes are divided into two groups, and different transition probability models are proposed. Finally, a prediction method of land use is proposed under the consideration of the changing structure of meshes. Though our proposed approach is a macroscopic forecasting method of land use, it is useful to evaluate the effects of urban policies for development projects.
Keywords: 330